Structure of the lepidopteran proboscis in relation to feeding guild. (20th November 2015) - Lehnert, Matthew S.; Beard, Charles E.; Gerard, Patrick D.; Kornev, Konstantin G.; Adler, Peter H.
ABSTRACT: Most butterflies and moths (Lepidoptera) use modified mouthparts, the proboscis, to acquire fluids. We quantified the proboscis architecture of five butterfly species in three families to test the hypothesis that proboscis structure relates to feeding guild. We used scanning electron microscopy to elucidate the fine structure of the proboscis of both sexes and to quantify dimensions, cuticular patterns, and the shapes and sizes of sensilla and dorsal legulae. Sexual dimorphism was not detected in the proboscis structure of any species. A hierarchical clustering analysis of overall proboscis architecture reflected lepidopteran phylogeny, but did not produce a distinct group of flower visitors or of puddle visitors within the flower visitors. Specific characters of the proboscis, nonetheless, can indicate flower and nonflower visitors, such as the configuration of sensilla styloconica, width of the lower branches of dorsal legulae, presence or absence of dorsal legulae at the extreme apex, and degree of proboscis tapering. We suggest that the overall proboscis architecture of Lepidoptera reflects a universal structural organization that promotes fluid uptake from droplets and films. On top of this fundamental structural organization, we suggest that the diversity of floral structure has selected for structural adaptations that facilitate entry of the proboscis into floral tubes. J. Morphol. 277:167–182, 2016. © 2015 Wiley Periodicals, Inc.